A CIDADE EM MOVIMENTO: EXPERIÊNCIA DOS TRABALHADORES - MIGRANTES NAS FAVELAS DO ANEL VIÁRIO E DO BAIRRO LAGOINHA EM UBERLÂNDIA-MG (1990-1997) (Revista de História Regional, 2007)
This article suggests to reflect about migrates workers that live Anels and Lagoinhas shantytown. It will be described of his experience, lifes trajectory what do they think about the city and what the newspapers registered how wove community white the migratory flood to Uberlândia.